Bestimmung von Polypeptiden und Aminosäuren durch Omegaphorese - E. Schumacher; P. Ryser (CHIMIA)
Omegaphoresis is an electrophoretic method based on Kohlrausch’s ω-function. Detection and estimation of aminoacids and polypeptides in mixtures at the nano- to picomol-level is described. Duration of analysis is less than 5 min.